COMPARISON OF BLEEDING RISKS WITH NEW ORAL ANTICOAGULANTS VERSUS ACENOCUMAROLUM – part 1 - Roxana Radu; Octavian Dincă; Cristina Pădurariu; Tiberiu Niță; Cristian Vlădan; Alexandru Bucur (Romanian Journal of Oral Rehabilitation, 2022)
Aim of the study Oral anticoagulants are effective therapies for reduction of stroke risk in patients with atrial fibrillation. However, blocking elements of the clotting cascade carries an inherent risk of bleeding. Also, anticoagulated patients sometimes require tooth extractions and other invasive procedures. The purpose of the present study was to compare the relationship between the risk factors and postoperative hemorrhage among dental patients with atrial fibrillation receiving acenocumarolum versus new oral anticoagulants users.